Co-expression of a SARP Family Activator ChlF2 and a Type II Thioesterase ChlK Led to High Production of Chlorothricin in Streptomyces antibioticus DSM 40725 - Li, Yue; Zhang, Jihui; Zheng, Jiazhen; Guan, Hanye; Liu, Wen; Tan, Huarong (Frontiers in Bioengineering and Biotechnology, 2020)
Chlorothricin (CHL), produced by Streptomyces antibioticus DSM 40725 (wild type strain, WT), belongs to a growing family of spirotetronate antibiotics that have biological activities inhibiting pyruvate carboxylase and malate dehydrogenase. ChlF2, a cluster-situated SARP regulator, can activate the transcription of chlJ, chlC3, chlC6, chlE1, chlM and chlL to control CHL biosynthesis. Co-expression of chlF2 and chlK encoding type II thioesterase in WT strain under the control of Pkan led to high-production of chlorothricin by 840% in comparison with that of WT. Since the inhibitory activity of CHL against several Gram-positive bacteria is higher than des-CHL, combinatorial strategies were applied to promote the conversion of des-CHL to CHL. Over-expression of chlB4 encoding halogenase combining with the supplementation of sodium chloride led to further 41% increase of CHL production compared to that of F2OE, a chlF2 over-expression strain. These findings provide new insights into the fine-tuned regulation of spirotetronate family of antibiotics and the construction of high-yield engineered strains.